(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Constitution is rightly the most critical touchstone for deciding the scope of women’s rights in the post-independence period. The provisions of adult franchise, non-discrimination based on sex and positive discrimination (or governmental policy regarding minorities in society) for women and children set Indian women a long ways in front of huge numbers of their western counterparts. Equality and non-discrimination wound up fundamental and enforceable legal rights. The scope of Article 21, could be extended to peruse into it issues of Social and Economic Justice. It is against this background we inspect the Major Law Reform of the Post-independence period. This critical goal could be accomplished just by weakening women’s rights to touch base at a dimension of least accord so the agenda of change could be influenced absent much resistance. A few Customary rights were relinquished to touch base at consistency. The Statutes that were at long last enacted were simply ornamental as opposed to being markers of certified and solid endeavors at correcting the gender discrimination composed into the Hindu law. A portion of the irregularities inside the changed laws, just as the mind boggling and relentless procedure of the change is inspected here in this Article to dissect the stilted endeavors of the Hindu law Reforms for gender justice or gender equality in all angles.